The Buddhist Principle in Budget Management - บุญปู่ สมศักดิ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
Budget management is a significant burden and duty in organizational and institutional management. It is necessary to set up a budget plan making carefully and efficiently in order to spend the limited budget effectively. The Buddhist principle in budget management consists of 5 steps; 1. Financial or budget plan, 2. Organizational management, 3. Budget earning and protecting, 4. Budget management, and 5. Budget spending. The Buddhist principles necessary to budget management are the principles of Temporal Welfare and the principles of Bhogadiya or possession consumption.